Polineuropatías desmielinizantes crónicas: dificultades en el diagnóstico electrofisiológico - Hughes G., Ricardo (Revista Hospital Clínico Universidad de Chile, 2007)
Chronic demyelinating polyneuropathies are a group of disease with a difficult differential diagnosis especially if they are axonal, demyielinating, hereditary or adquired. The clinical electrophisiology and laboratories study can help to classificated and to determinate if are susceptible to treat. We described the types of demyelinating polyneuropathies and the clinical and electrophisyology criteria used to diagnosis, remarking the limitation of these criteria.